Could onomatopoeic words be what our ancestors first spoke? - Mohamad Radzi Mustafa (Journal of Modern Languages)
The main focus of this paper is the argument for the evolution of language from onomatopoeic words. To support this view, the idea that language evolved to fulfill acts of communication has been disputed. If language is viewed in such a light, then whatever theories researchers put forward have to grapple with the paradox that if language is initially communicative then how would the listener know what the speaker meant. The speaker would also not know what word to invent to represent his thoughts in the first place. By imitating sounds from the natural habitat, protohumans were able to articulate their first words. The seemingly communicative intent of these words would reside in the 'interactive' meaning protohumans perceived from the sound structures of these words and the naturally occurring referents (objects being referred to) that the sound structures mapped onto. Communication, after all, is a by-product of perception. Therefore, to view the evolution of protolanguage